Preparation method and application of Cu / Cu2O Yolk-shell structure composite material
Through the design of Cu/Cu2O Yolk-shell structural composite material, Cu is used to enhance the photocatalytic performance of Cu2O, and efficient removal of multivalent iodine is achieved, solving the problem of full-valent iodine removal in the existing technology, and improving the utilization of copper rate and material stability.
Patent Information
- Application Number
- CN202411301051.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to efficiently remove the polyvalent radioactive iodine released in the environment at the same time, especially the high-valent iodine. Traditional physical adsorbent materials have low selectivity, and chemical precipitation materials are prone to inactivation, making it difficult to achieve synchronous and efficient removal of full-valent iodine.
Cu/Cu2O Yolk-shell structure composite material is used to enhance the photocatalytic performance of Cu2O through Cu, photocatalytic reduction of high-valent iodine, and use Cu/Cu2O to adsorb low-valent iodine to achieve effective removal of multivalent iodine. The material design is The Yolk-shell structure with Cu as the core and Cu2O as the shell improves the utilization rate of copper and the recycling ability of materials.
It realizes efficient adsorption and removal of multivalent iodine, improves the stability and reuse ability of traditional copper-based materials, and improves the removal performance of full-valent radioactive iodine.
Smart Images

Figure CN119303574A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage purification in environmental protection, and in particular to a preparation method of a Cu / Cu2O Yolk-shell structure composite material and application thereof in adsorbing multivalent iodine. Background Art
[0002] In addition to nuclear accidents, spent fuel reprocessing, medical radiotherapy, nuclear testing, etc. are also easily released into the ecological environment. The types and valence states of radioactive iodine are relatively abundant (such as I − , I2, IO− 3, etc.), which are easily converted into each other in the environment. Therefore, it is necessary to simultaneously and efficiently remove the radioactive multivalent iodine released into the environment.
[0003] For single-valent radioactive iodine (mainly I − There are many reports on the removal of radioactive iodine (I2), which can be divided into physical adsorption and chemical precipitation. However, there are basically no reports on the simultaneous and efficient removal of all valence states of iodine, especially high-valence states of iodine (HIO, IO− 3). Because the molecular sizes of various forms of iodine are inconsistent, and the pores of traditional physical adsorption materials (such as activated carbon and zeolite molecular sieves) are generally 10~30 Å, their selective adsorption efficiency for radioactive iodine is low in the actual environment where interfering ions exist. The constructed covalent organic framework materials, porous organic polymers, metal-organic framework materials and other new organic porous materials have a pore size distribution that matches the target valence state of iodine and contain electron-rich heterocycles such as N and S. Although they can efficiently and selectively adsorb I − or I2, but the removal capacity of other valence states of iodine is insufficient, and it is easily degraded and inactivated by high-energy irradiation. Therefore, traditional physical adsorption is difficult to be actually applied to the simultaneous and efficient removal of all-valence states of radioactive iodine.
[0004] Chemical precipitation is a method of effectively removing iodine by forming insoluble compounds with metal ions and part of the valence state of iodine, such as AgI, AgIO3, Hg2I2, Hg2(IO3)2, PbI2, CuI, etc. It has the advantages of high selectivity and removal efficiency. Affected by the toxicity of heavy metals Hg and Pb and the cost of precious metal Ag, copper is the most promising material in the practical application of radioactive iodine removal. However, copper-based materials are prone to form a dense layer of CuO on the surface and become inactivated, which has long hindered their application in iodine removal. Professor Zhang Guanghui's team at Tianjin University inhibited the surface oxidation of CuCl by adding a deoxidizer (Na2SO3) and significantly improved its adsorption performance. Therefore, solving the problem of oxidation and inactivation of the surface layer of copper-based materials is a prerequisite for its practical application in radioactive iodine removal. Professor Robshaw's team at the University of Sheffield in the UK loaded Cu on diamine chelating resin, and used the chemical adsorption of copper and the physical adsorption of resin to synergistically and efficiently remove 2940±180 mg / g of iodine ions. Research conducted by Yan Taihong's team at the China Institute of Atomic Energy shows that due to the redox mechanism during the adsorption process, zero-valent copper has a significantly better performance than Cu in removing iodine from spent fuel reprocessing waste gas. + Cu 2+ Therefore, by controlling the valence state of copper in the composite material, it is expected to solve the problem of the difficulty in simultaneously and efficiently removing the full-valence radioactive iodine selectively. Summary of the invention
[0005] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a preparation method and application of a Cu / Cu2O Yolk-shell structure composite material, which enhances the semiconductor properties of Cu2O by Cu in the material, photocatalytically reduces high-valent iodine (such as HIO, IO− 3, etc.), and then uses Cu / Cu2O to adsorb low-valent iodine (I − The invention realizes the effective adsorption of multivalent iodine; compared with the traditional copper-based adsorbent, the Yolk-shell structure can also make the utilization rate of copper higher, providing a technical reference for the removal of radioactive multivalent iodine in wastewater.
[0006] Technical solution: On the one hand, the present invention provides a method for preparing a Cu / Cu2O Yolk-shell structure composite material, comprising the following steps: S1: After copper sulfate, polyvinyl pyrrolidone K-30 and water are mixed evenly, trisodium citrate and sodium carbonate are added dropwise, stirred evenly, and then ascorbic acid is added, heated, cooled, centrifuged, washed, and dispersed in deionized water to obtain a Cu core solution; S2: placing styrene and the Cu core solution in a polyvinyl pyrrolidone K-30 aqueous solution, bubbling with nitrogen, heating and stirring, then adding a K2S2O8 aqueous solution, stirring, and cooling to obtain an emulsion Cu core / polystyrene sphere; S3: placing the emulsion Cu core / polystyrene sphere, CuCl2 and ammonia water in deionized water, stirring, then adding ascorbic acid thereto, continuing to stir the reaction, centrifugally drying, soaking in N,N-dimethylformamide, washing, and drying to obtain a Cu / Cu2O Yolk-shell structure composite material.
[0007] Furthermore, in S1, the mass ratio of the copper sulfate, water, polyvinyl pyrrolidone K-30, trisodium citrate, sodium carbonate and ascorbic acid is 1:100~300:2~5:1.5~2.5:0.5~1.5:2~3.
[0008] Furthermore, in S1, the specific conditions of the heating are: heating in a water bath at 60-90°C for 1.5-3 h.
[0009] Furthermore, in S1, the solid-liquid mass ratio of the Cu core solution is 1:10-30.
[0010] Furthermore, in S2, the mass ratio of K2S2O8, water, styrene, polyvinylpyrrolidone K-30 and Cu core solution is 1:450~650:55~75:1.5~3.5:1.2~2.
[0011] Furthermore, the styrene is styrene washed with 10 wt % NaOH solution and deionized water.
[0012] Furthermore, in S2, the specific conditions of the heating are: heating at 60-90°C for 18-36 hours.
[0013] Furthermore, in S3, the mass ratio of the CuCl2, deionized water, emulsion Cu core / polystyrene sphere, ammonia water and ascorbic acid is 1:500~800:30~50:10~15:10~15.
[0014] On the other hand, the present invention provides a use of a Cu / Cu2O Yolk-shell structure composite material prepared by any of the methods described above in the adsorption of multivalent iodine, wherein the Cu / Cu2O Yolk-shell structure composite material is put into a water body containing multivalent iodine to be adsorbed, illuminated for a period of time, and then adsorbed in the dark.
[0015] Furthermore, the Cu / Cu2O Yolk-shell structure composite material after dark adsorption is heated at 100-110°C for 10-12h, then dispersed in deionized water and illuminated for 2-3h, centrifuged, filtered, washed, and dried, and then used again for polyvalent iodine adsorption. Because iodine is easy to volatilize after heating, the Cu / Cu2O Yolk-shell structure composite material after adsorbing polyvalent iodine is heated to release part of the iodine, and then the Cu / Cu2O Yolk-shell structure composite material is used to reduce CuI to elemental Cu by irradiation with light, thereby releasing the remaining iodine, thereby realizing the recycling of materials.
[0016] Furthermore, the amount of the Cu / Cu2O Yolk-shell structure composite material added to the water body is 0.25-2 g·L -1 ; The illumination time is 1 to 2 h; The dark adsorption time is 2 to 12 h.
[0017] Beneficial effects: The present invention uses single copper as the core, covers the surface with polystyrene, and then prepares a Cu2O shell on the periphery. The polystyrene hard template is eluted by N, N-dimethylformamide to prepare a Cu / Cu2O Yolk-shell structure composite material with photocatalytic and adsorption functions. The mechanism of photocatalytic adsorption of multivalent iodine by the material is as follows: (1) Using the photoelectrochemical cathode protection technology, under light conditions, the photocatalytic reduction performance of Cu / Cu2O is used to generate photoinduced electrons to inhibit the oxidation corrosion of the copper surface, thereby ensuring the stable existence of single copper; (2) Under visible light, through the photocatalytic reduction technology, the photoinduced electrons generated by the photocatalytic reduction performance of Cu / Cu2O are used to photocatalytically reduce high-valent iodine (such as IO−3, HIO, I2, etc.) to a single low-valent iodine (I − ); (3) In a dark environment, elemental copper efficiently adsorbs low-valent iodine through redox reactions; (4) Under the synergistic effect of light and heating, the thermal precipitation of iodine in the adsorbed material and the photocatalytic regeneration of the adsorption material (copper reduction and iodine release) are promoted, which stimulates the recycling and regeneration function of the photocatalytic adsorption material, improves the defect of the traditional chemical precipitation method that is difficult to reuse, and enhances the removal performance of copper for fully valent radioactive iodine.
[0018] Compared with the prior art, the specific beneficial effects of the present invention are as follows: The present invention prepares a Cu / Cu2O hollow Yolk-shell structure composite material with Cu as the core and Cu2O as the shell, which has good photocatalytic reduction and iodine adsorption properties. The present invention enhances the semiconductor properties of Cu2O through the Cu in the material, photocatalytically reduces high-valent iodine (such as HIO, IO− 3, etc.), and then uses Cu / Cu2O to adsorb low-valent iodine (I− and I2), achieving effective adsorption and removal of multivalent iodine; compared with traditional copper-based adsorbents, the Cu / Cu2O composite material prepared by the present invention is a Yolk-shell hollow structure, and the copper in the center that is not easy to participate in the reaction is removed, thereby increasing the copper utilization rate and improving the defect of the traditional chemical precipitation method that is difficult to reuse. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 is a SEM image of the Cu / Cu2O Yolk-shell structure composite material prepared in Embodiment 1; Figure 2 TEM image of the Cu / Cu2O Yolk-shell structure composite material prepared in Embodiment 1; Figure 3 XRD spectrum of the Cu / Cu2O Yolk-shell structure composite material prepared in Implementation Example 1; Figure 4 is an adsorption curve of iodine by the Cu / Cu2O Yolk-shell structure composite material prepared in Implementation Example 1; Figure 5 TEM image of the Cu / Cu2O Yolk-shell structure composite material prepared in Embodiment 2; Figure 6 XRD spectrum of the Cu / Cu2O Yolk-shell structure composite material prepared in Implementation Method 2; Figure 7 is an adsorption curve of iodine by the Cu / Cu2O Yolk-shell structure composite material prepared in Implementation Example 2; Figure 8 TEM image of the Cu / Cu2O Yolk-shell structure composite material prepared in Embodiment 3; Fig. 9 The XRD spectrum of the Cu / Cu2O Yolk-shell structure composite material prepared in Embodiment 3; Fig.10 This is a graph showing the adsorption of iodine by the Cu / Cu2O Yolk-shell structure composite material prepared in Implementation Example 3. DETAILED DESCRIPTION
[0020] The present invention is described in detail below in conjunction with the embodiments.
[0021] Implementation 1: This embodiment provides a method for preparing a Cu / Cu2O Yolk-shell structure composite material, which is specifically as follows: 1 mL of 0.68 M copper sulfate and 0.3 g of polyvinyl pyrrolidone K-30 were added to 17 mL of deionized water. After magnetic stirring for 10 min, 1 mL of a mixed solution of 0.74 M trisodium citrate and 1.2 M sodium carbonate was added dropwise. After stirring for 10 min, 1 mL of 1.4 M ascorbic acid solution was added dropwise. The mixture was heated in a water bath at 80 ºC for 2 h to obtain a brown-red precipitate. After cooling to room temperature, the mixture was centrifuged and washed three times with deionized water and anhydrous ethanol respectively, and then dispersed in 20 mL of deionized water to obtain a Cu core solution.
[0022] 80 mL of styrene was washed thoroughly with 20 mL of 10 wt% NaOH solution and deionized water to remove the stabilizer; 78 mL of the washed styrene was added to a three-necked round-bottom flask containing 600 mL of 0.5wt% PVP aqueous solution, 2 mL of the above-mentioned Cu core solution was added, nitrogen was bubbling for 15 min, and magnetic stirring was performed at 75°C for 30 min. 60 mL of an aqueous solution containing 1.2 g of K2S2O8 was quickly added to the flask to initiate the polymerization reaction of styrene. After stirring the reaction for 24 h, it was cooled to room temperature to obtain an emulsion product of Cu core / polystyrene spheres.
[0023] 2 mL of Cu core / polystyrene spheres, 2 mL of 0.2 M CuCl2 solution and 0.6 mL of 7 M ammonia water were added to a vial containing 25 mL of water. After stirring for 1 h, 6 mL of 0.6 M ascorbic acid solution was added to the above solution and the reaction was continued for 1 h under stirring at room temperature. Finally, after the precursor was completely reduced, the product was centrifuged and dried. The dried product was soaked in N, N dimethylformamide to remove the PS spheres, and then washed with ethanol three times. After vacuum drying at 60 ° C, the Cu / Cu2O Yolk-shell structure composite material was obtained.
[0024] The morphology of the Cu / Cu2O Yolk-shell structure composite material prepared in this embodiment was observed by SEM ( Figure 1 ), indicating the hollow structure of the prepared Cu / Cu2O Yolk-shell structure composite material. Figure 2 3 is a TEM picture of the Cu / Cu2O Yolk-shell structure composite material prepared in this embodiment. It can be seen that the structure of the material is a Yolk-shell structure. Figure 3 : is the XRD spectrum of the Cu / Cu2O Yolk-shell structure composite material prepared in this embodiment, which can confirm that the composition of the composite material is Cu and Cu2O.
[0025] This embodiment also provides an application of a Cu / Cu2O Yolk-shell structure composite material, as follows: 50 mg of the Cu / Cu2O Yolk-shell structure composite material prepared above was added to 50 mL of a solution containing 0.1 mM I2 (10% methanol solution) and 0.20 mM iodide ions, illuminated for 2 h at room temperature and then adsorbed in the dark, and the residual iodine concentration in the solution was measured by ICP. Figure 4 The adsorption results showed that the Cu / Cu2O Yolk-shell structure composite material reached adsorption equilibrium within 50 min, and the adsorption efficiency reached 86.76%.
[0026] 40 mg of the dried product after adsorption of polyvalent iodine was heated at 110 °C for 12 h, then dispersed in deionized water, exposed to light at room temperature for 2 h, centrifuged, filtered and separated, washed with deionized water and anhydrous ethanol, and vacuum freeze-dried to obtain a reactivated Cu / Cu2O Yolk-shell structure composite material, which can be used again for polyvalent iodine adsorption.
[0027] 20 mg of the reactivated Cu / Cu2O Yolk-shell structure composite material was added to 20 mL of a solution containing 0.1 mM I2 (10% methanol solution) and 0.20 mM iodine ions, and then adsorbed in the dark at room temperature for 2 hours. The residual iodine concentration in the solution was measured by ICP. The adsorption efficiency of the Cu / Cu2O Yolk-shell structure composite material can still reach 81.43%.
[0028] Implementation 2: This embodiment provides a method for preparing a Cu / Cu2O Yolk-shell structure composite material, which is specifically as follows: 1 mL of 0.68 M copper sulfate and 0.45 g of polyvinyl pyrrolidone K-30 were added to 25 mL of deionized water. After magnetic stirring for 10 min, 1.5 mL of a mixed solution of 0.74 M sodium trisodium citrate and 1.2 M sodium carbonate was added dropwise. After stirring for 10 min, 1.5 mL of 1.4 M ascorbic acid solution was added dropwise. The mixture was heated in a water bath at 90 ºC for 3 h to obtain a brown-red precipitate. After cooling to room temperature, the mixture was centrifuged and washed three times with deionized water and anhydrous ethanol respectively, and then dispersed in 30 mL of deionized water to obtain a Cu core solution.
[0029] 150 mL of styrene was washed thoroughly with 50 mL of 10 wt% NaOH solution and deionized water to remove the stabilizer. 135 mL of washed styrene was added to a three-necked round-bottom flask containing 1000 mL of 0.5 wt% PVP aqueous solution, and 3.5 mL of the above Cu core solution was added. After nitrogen bubbling for 15 min, magnetic stirring was performed at 90 °C for 30 min, and 60 mL of aqueous solution containing 1.2 g K2S2O8 was quickly added to the flask to initiate the polymerization reaction of styrene; after stirring the reaction for 36 h, it was cooled to room temperature to obtain a milky product of Cu core / polystyrene spheres.
[0030] 2.5 mL of Cu core / polystyrene spheres, 2 mL of 0.2 M CuCl2 solution and 0.75 mL of 7 M ammonia water were added to a vial containing 30 mL of water. After stirring for 1 h, 7.5 mL of 0.6 M ascorbic acid solution was added to the above solution and the reaction was continued under stirring at 90 °C for 1.5 h. Finally, after the precursor was completely reduced, the product was centrifuged and dried. The dried product was soaked in N, N-dimethylformamide to remove the PS spheres, then washed three times with ethanol and dried in vacuum at 60 °C to obtain a Cu / Cu2O Yolk-shell structure composite material.
[0031] Figure 5 3 is a TEM picture of the Cu / Cu2O Yolk-shell structure composite material prepared in this embodiment. It can be seen that the structure of the material is a Yolk-shell structure. Figure 6 : is the XRD spectrum of the Cu / Cu2O Yolk-shell structure composite material prepared in this embodiment, which can confirm that the composition of the composite material is Cu and Cu2O.
[0032] This embodiment also provides an application of a Cu / Cu2O Yolk-shell structure composite material, as follows: 25 mg of the Cu / Cu2O Yolk-shell structure composite material prepared above was added to 100 mL of a solution containing 0.2 mM iodide ions and 0.10 mM iodate ions. The solution was exposed to light for 2 h at room temperature and then adsorbed in the dark. The residual iodine concentration in the solution was measured by ICP. Figure 7 The adsorption results showed that the Cu / Cu2O Yolk-shell structure composite material reached adsorption equilibrium within 50 min, and the adsorption efficiency reached 76.57%.
[0033] Implementation 3: This embodiment provides a method for preparing a Cu / Cu2O Yolk-shell structure composite material, which is specifically as follows: 1 mL of 0.68 M copper sulfate and 0.15 g of polyvinyl pyrrolidone K-30 were added to 8 mL of deionized water. After magnetic stirring for 10 min, 0.5 mL of a mixed solution of 0.74 M sodium trisodium citrate and 1.2 M sodium carbonate was added dropwise. After stirring for 10 min, 0.5 mL of 1.4 M ascorbic acid solution was added dropwise. The mixture was heated in a water bath at 60 ºC for 1.5 h to obtain a brown-red precipitate. After cooling to room temperature, the precipitate was separated by centrifugation, washed three times with deionized water and anhydrous ethanol respectively, and then dispersed in 10 mL of deionized water to obtain a Cu core solution.
[0034] 40 mL of styrene was washed thoroughly with 20 mL of 10 wt.% NaOH solution and deionized water to remove the stabilizer. 38 mL of washed styrene was added to a three-necked round-bottom flask containing 300 mL of 0.5 wt.% PVP aqueous solution, and 1 mL of the above Cu core solution was added. After nitrogen bubbling for 15 min, magnetic stirring was performed at 60°C for 30 min, and 60 mL of aqueous solution containing 1.2 g K2S2O8 was quickly added to the flask to initiate the polymerization reaction of styrene; after stirring the reaction for 18 h, it was cooled to room temperature to obtain a milky product of Cu core / polystyrene spheres.
[0035] 1.5 mL of Cu core / polystyrene spheres, 2 mL of 0.2 M CuCl2 solution and 0.5 mL of 7 M ammonia water were added to a vial containing 20 mL of water. After stirring for 1 h, 5 mL of 0.6 M ascorbic acid solution was added to the above solution, and the reaction was continued for 0.5 h under stirring at 20°C. Finally, after the precursor was completely reduced, the product was centrifuged and dried. The dried product was soaked in N, N-dimethylformamide to remove the PS spheres, and then washed three times with ethanol. After vacuum drying at 60°C, the Cu / Cu2O Yolk-shell structure composite material was obtained.
[0036] Figure 8 3 is a TEM picture of the Cu / Cu2O Yolk-shell structure composite material prepared in this embodiment. It can be seen that the structure of the material is a Yolk-shell structure. Fig. 9 : is the XRD spectrum of the Cu / Cu2O Yolk-shell structure composite material prepared in this embodiment, which can confirm that the composition of the composite material is Cu and Cu2O.
[0037] This embodiment also provides an application of a Cu / Cu2O Yolk-shell structure composite material, as follows: 50 mg of the Cu / Cu2O Yolk-shell structure composite material prepared above was added to 25 mL of a solution containing 0.1 mM iodate, 0.1 mM I2 (10% methanol solution) and 0.10 mM iodide ion, and then illuminated for 2 h at room temperature and adsorbed in the dark. The residual iodine concentration in the solution was measured by ICP. Fig.10 The adsorption results showed that the Cu / Cu2O Yolk-shell structure composite material reached adsorption equilibrium within 50 min, and the adsorption efficiency reached 81.57%.
[0038] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Cu / Cu2O Yolk-shell structure composite material, characterized in that: The following steps are involved: S1: After copper sulfate, polyvinyl pyrrolidone K-30 and water are mixed evenly, trisodium citrate and sodium carbonate are added dropwise, stirred evenly, and then ascorbic acid is added, heated, cooled, centrifuged, washed, and dispersed in deionized water to obtain a Cu core solution; S2: placing styrene and the Cu core solution in a polyvinyl pyrrolidone K-30 aqueous solution, bubbling with nitrogen, heating and stirring, then adding a K2S2O8 aqueous solution, stirring, and cooling to obtain an emulsion Cu core / polystyrene sphere; S3: placing the emulsion Cu core / polystyrene sphere, CuCl2 and ammonia water in deionized water, stirring, then adding ascorbic acid thereto, continuing to stir the reaction, centrifugally drying, soaking in N,N-dimethylformamide, washing, and drying to obtain a Cu / Cu2O Yolk-shell structure composite material.
2. The method for preparing the Cu / Cu2O Yolk-shell structure composite material according to claim 1, characterized in that: In S1, the mass ratio of the copper sulfate, water, polyvinyl pyrrolidone K-30, trisodium citrate, sodium carbonate and ascorbic acid is 1:100-300:2-5:1.5-2.5:0.5-1.5:2-3.
3. The method for preparing the Cu / Cu2O Yolk-shell structure composite material according to claim 1, characterized in that: In S1, the specific conditions of the heating are: heating in a water bath at 60-90°C for 1.5-3 h; In S1, the solid-liquid mass ratio of the Cu core solution is 1:10-30.
4. The method for preparing the Cu / Cu2O Yolk-shell structure composite material according to claim 1, characterized in that: In S2, the mass ratio of K2S2O8, water, styrene, polyvinylpyrrolidone K-30 and Cu core solution is 1:450~650:55~75:1.5~3.5:1.2~2.
5. The method for preparing the Cu / Cu2O Yolk-shell structure composite material according to claim 4, characterized in that: The styrene is styrene that has been washed with a 10 wt % NaOH solution and deionized water.
6. The method for preparing the Cu / Cu2O Yolk-shell structure composite material according to claim 1, characterized in that: In S2, the specific conditions of the heating are: heating at 60-90°C for 18-36 hours.
7. The method for preparing the Cu / Cu2O Yolk-shell structure composite material according to claim 1, characterized in that: In S3, the mass ratio of CuCl2, deionized water, emulsion Cu core / polystyrene sphere, ammonia water and ascorbic acid is 1:500~800:30~50:10~15:10~15.
8. An application of the Cu / Cu2O Yolk-shell structure composite material prepared by the method according to any one of claims 1 to 7 in the adsorption of multivalent iodine, characterized in that: The Cu / Cu2O Yolk-shell structure composite material is put into a water body containing multivalent iodine to be adsorbed, illuminated for a period of time, and then adsorbed in the dark.
9. The use of the Cu / Cu2O Yolk-shell structure composite material according to claim 8 in the adsorption of multivalent iodine, characterized in that: The Cu / Cu2O Yolk-shell structure composite material after dark adsorption is heated at 100-110°C for 10-12h, dispersed in deionized water, illuminated for 2-3h, centrifuged, filtered, washed and dried, and then can be used for multivalent iodine adsorption again.
10. The use of the Cu / Cu2O Yolk-shell structure composite material according to claim 8 in the adsorption of multivalent iodine, characterized in that: The amount of the Cu / Cu2O Yolk-shell structure composite material added to the water body is 0.25-2 g·L -1 ; The illumination time is 1 to 2 h; The dark adsorption time is 2 to 12 h.